Business subsidies in Finland: The dynamics of application and acceptance stages - Heli Koski; Jukka Tuuli (The Research Institute of the Finnish Economy (ETLA), 2010)
We use a comprehensive database concerning the application and allocation of business subsidies in Finland merged with the firm-level data comprising about 330 000 firms from the year 2004 to 2008. We find strong continuities in participation both within and between the different public support programs. Continuity in the firms' participation in the same support programs arises both from the application and acceptance stages. A firm that has once received subsidy from an agency, tends to apply it again, and it also seems that the agencies target their support to the firms they have previously subsidized. We further find that the firms that have once entered the Finnish subsidy system not only actively seek further support from the same organization but also from the other agencies allocating busi-ness subsidies. In addition, a firm's probability to apply subsidy from one agency is posi-tively related to its probability to apply subsidy simultaneously from another agency. In line with the previous empirical findings, and against the general public policy aims to target particular support for the SMEs, we find that all agencies favor larger companies. Also, contradictory to the learning hypothesis related to firm age, and on the other hand, supporting public policy lines favoring newly established or start-up companies in subsidy funding decisions, we find that younger firms both are more likely to apply for and to receive subsidies than the older ones.
Keywords: D21; L53; O25; 330; business subsidies; selection process; continuity